Microtubule-Targeting 7-Deazahypoxanthines Derived from Marine Alkaloid Rigidins: Exploration of the N3 and N9 Positions and Interaction with Multi-Drug Resistance Proteins - Dasari, Ramesh (ChemMedChem, 2019)
Our laboratories have been investigating synthetic analogues of marine alkaloid rigidins possessing promising anticancer activities. These analogues, based on the 7-deazahypoxanthine skeleton are available in one- or two-step synthetic sequences and exert cytotoxicity by disrupting microtubule dynamics in cancer cells. In the present work we extended the available structure-activity relationship data to N3- and N9-substituted derivatives. Although the N3-substitution results in a loss of activity, the N9-substituted compounds retain the nanomolar antiproliferative activities and antitubulin mode of action of the original unsubstituted compounds. Furthermore, work reported herein also demonstrated that MDR proteins do not confer resistance to both N9-unsubstituted and substituted compounds. It was found that sublines overexpressing ABCG2, ABCC1 and ABCB1 proteins were equally responsive to the rigidin analogues as their parental cell lines. Thus, the study reported herein provides further impetus to investigate the rigidin-inspired 7-deazahypoxanthines as promising anticancer agents.